2020
DOI: 10.3389/fendo.2020.00541
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of the Kuruma Prawn Marsupenaeus japonicus Reveals Possible Peripheral Regulation of the Ovary

Abstract: Crustacean reproduction has been hypothesized to be under complex endocrinological regulation by peptide hormones. To further improve our understanding of the mechanisms underlying this complex regulation, knowledge is needed regarding the hormones not only of the central nervous system (CNS) such as the X-organ/sinus gland (XOSG), brain, and thoracic ganglia, but also the peripheral gonadal tissues. For example, in vertebrates, some gonadal peptide hormones including activin, inhibin, follistatin, and relaxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 88 publications
(144 reference statements)
1
15
0
Order By: Relevance
“…GPCRs are characterized by seven transmembrane domains, an external N-terminal domain, and a C-terminal cytosolic domain (25). These are divided among three large classes: rhodopsin-like (Class A), which represents the largest number of GPCRs; secretinlike (Class B); and metabotropic glutamate (Class C) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: G Protein-coupled Receptor-mediated Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…GPCRs are characterized by seven transmembrane domains, an external N-terminal domain, and a C-terminal cytosolic domain (25). These are divided among three large classes: rhodopsin-like (Class A), which represents the largest number of GPCRs; secretinlike (Class B); and metabotropic glutamate (Class C) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: G Protein-coupled Receptor-mediated Signalingmentioning
confidence: 99%
“…Dilp8 is one of eight insulin-like peptides (ILPs) in D. melanogaster (74)(75)(76)(77)(78). The ILP superfamily consists of insulin, insulin-like growth factors (IGFs), and relaxin-like peptides (38,71). Dilp 1 to 6 are in the insulin/IGF clade and bind to receptor tyrosine kinase receptors; Dilp 7 and 8 are in the relaxin-like clade and bind to leucine-rich repeat GPCRs (71,74,75).…”
Section: Leucine-rich Repeat Receptor and Insulin-like Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Orexin is involved in the regulation of the reproductive system through the hypothalamic-pituitary-ovarian axis ( 79 ), and the transcriptome profile of the endometrium during early pregnancy in pigs has revealed that orexin affected the expression of a large number of genes differentially ( 79 ) while transcriptome of myometrial explants during the early implantation period suggested that orexin influenced the process involved in quiescence, proliferartion, remodeling and angiogenesis in myometrial explants during the peri-implantation period in the pig ( 80 ). NPY has also been found to be involved in gonadal development in crustaceans ( 31 ) and mammals ( 32 ). CCK receptor (CCKAR and CCKBR) deletion leads to abnormal cortical development, and using comparative transcriptomic analysis, transcripts of CXCL12, BMP7 are downregulated and may be target genes for abnormal cortical development ( 86 ).…”
Section: Neuropeptidomics and Gene Editingmentioning
confidence: 99%
“…For example, in the shrimp M. ensis, in vivo gene silencing of neuroparsins could cause a significant decrease in vitellogenin transcript level in the hepatopancreas and ovary (Yang et al, 2014). In Marsupenaeus japonicus, in vivo injection of recombinant neuroparsin could increase the expression of MjVg (Tsutsui et al, 2020).…”
Section: Introductionmentioning
confidence: 99%